Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d1nh00629k
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced photoresponse of single silver nanowires and their network devices

Abstract: Photo-bolometric effect is critically important in optoelectronic structures and devices employing metallic electrodes with nanoscale features due to heating caused by the plasmonic field enhancement. One peculiar case is individual...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…[47][48][49][50][51] The most well-defined fact of PP origin in the optical performance of a material is related to the presence of energy band gap between the valence and conduction band, wherein the charge carriers are excited due to the higher incident energy with the illumination of laser light than the energy band gap of the material. The observed PP mechanism in most of the nanostructures also is originated/enhanced through the surface plasmonic effects, [52][53][54][55][56][57][58] in which the laser light-induced excited or generated charge carriers collectively rise with the increment of the photocurrent. In comparison to PP, if the photocurrent decreases under the illumination of laser light, it is usually explained by the negative photoconductivity (NP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49][50][51] The most well-defined fact of PP origin in the optical performance of a material is related to the presence of energy band gap between the valence and conduction band, wherein the charge carriers are excited due to the higher incident energy with the illumination of laser light than the energy band gap of the material. The observed PP mechanism in most of the nanostructures also is originated/enhanced through the surface plasmonic effects, [52][53][54][55][56][57][58] in which the laser light-induced excited or generated charge carriers collectively rise with the increment of the photocurrent. In comparison to PP, if the photocurrent decreases under the illumination of laser light, it is usually explained by the negative photoconductivity (NP).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to PP, if the photocurrent decreases under the illumination of laser light, it is usually explained by the negative photoconductivity (NP). Depending upon the nature/type of nanodevices, in the presence of charge trapping centers, 52,53 defects, 54 surface plasmon polaritons, 55,56 the thermoplasmonic effect, 57 and the photon assisted electron-phonon scattering mechanism 58 cause the decrement in laser light-induced photocurrent or negative photoconductivity. In an earlier report, the superconducting niobium-nanostructured thin film 58 was used for the room temperature photodetection.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we fabricated substrate-engineered MoS 2 devices by mechanical exfoliation and dry transfer 21 of atomically thin MoS 2 akes on substrates (sapphire or oxidized silicon) with prepatterned trenches/holes formed by focused ion beam (FIB). We contacted the akes with Indium needles [22][23][24] which are suitable for achieving Ohmic contacts to MoS 2 25,26 (gold-contacted device measurements are shown in Supporting Information). A typical device is shown in Fig.…”
Section: Main Textmentioning
confidence: 99%
“…1d). Such bias-independent photoconductance is typically an indication for an photothermoelectric nature of the observed signal 22,24,[27][28][29] . Although we propose that the photocurrent in substrate-engineered MoS 2 devices is dominated by the photothermal effect (PTE) 30,31 , other possible mechanisms have been reported that may lead to a photovoltaic response.…”
Section: Main Textmentioning
confidence: 99%
“…Of various nanomaterials, metal nanowire (NW) networks exhibit fascinating characteristics for supercapacitor electrodes: they show remarkable electrical conductivity as a current collector and can also form a percolation network that provides excellent mechanical properties to be applied for the mechanically deformable electrode. 14 Due to the desirable characteristics of the metal NWs, there have been extensive studies that utilized metal NWs to develop highly advanced smart devices such as electromagnetic interference shielding, 15,16 physiological monitoring, 17 virtual reality haptic interface, 18 sensors, 19,20 and air lters. 21 Likewise for supercapacitors, a myriad of reports utilized metal NW networks as a current collector and deposited other supercapacitive materials such as metal oxides, 22,23 conductive polymers, 24,25 and hybrid composites 26 to fabricate core-shell NW-based supercapacitors.…”
Section: Introductionmentioning
confidence: 99%